Flow analysis in right-angled pipes with different geometric shapes and parameters for sludge discharge in slime shield machines measured using a CFD-DEM method. Issue 5 (29th August 2020) - Chen, Lumin; Liu, Kaixuan; Yao, Yufeng; Yao, Jun; Su, Zixue; Luo, Guofu
Abstract: Mud and gravel deposition often occurs in circulation systems of pumps. In this paper, a liquid-solid coupling method combining CFD and DEM is proposed to study two-phase flow behavior of water, The flow characteristics of water-clay mud and the motion characteristics of gravel were simulated under different discharge pipe bending radii and geometry shape conditions. Numerical results showed that for a circular cross section pipe with a fixed bending radius, the collision times between the gravel particles and the pipe wall decreased with the increase of the bending radius.